An Analysis of Figurative Language in Maher Zain’s 2013 Album: Educational Context in Islamic Songs - Yuliawati, Fitrah; Hasan, Moh. (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2023)
The aim of this analysis is focused on figurative language. Figurative language is very interesting to analyze because many people have difficulty in understanding about the types of figurative language and the meaning of lines or lyrics by using figurative language. The purpose of this research is to study an analysis of figurative language in Maher Zains Album 2013. This study uses descriptive qualitative research, because the data in the form of texts and Maher Zain songs lyrics which contain many types of figurative language. From 5 songs such as: hold my hand, Insya Allah, for the rest of my life, thank you Allah, and Palestine will be free. From these five songs the researcher found 10 figurative language namely: simile, metaphor, personification, litotes, antithesis, alliteration, euphemism, parallelism, hyperbole, irony. The conclusion of this research is there are some kinds of figurative language use by Maher Zain in his song. This study is very useful for other researchers who want to do research in figurative language analysis with other literary works.